Optical Biosensor Based on Microbendings Technique: An Optimized Mean to Measure the Bone Strength. (24th December 2014) - Singh, Preeti; Shrivastava, Abhishek
Abstract : Osteoporosis, a disease in humans, reduces bone mineral density. The microarchitecture of the bone gets deteriorated with change in variety of proteins in the bone. Therefore, a quantitative assessment of the strength of human bone, considering its structural properties and degradation due to aging, disease, and therapeutic treatment, becomes an integral part of the bioengineering studies. This paper presents a model of fiber optic biosensors (FOBs) which utilizes microbending technique to measure the strength of the bone. In parallel, an artificial neural network (ANN) based test bench has been developed for the optimization of FOBs strain measurement in orthoapplications using MATLAB. The performance accuracy of the given model appears to be considerable in ensuring the detection of the onset of osteoporosis.